Understanding digital signal processing with MATLAB and solutions - Poularikas, Alexander D. (The electrical engineering and applied signal processing series, 2018)
The book discusses receiving signals that most electrical engineers detect and study. The vast majority of signals could never be detected due to random additive signals, known as noise, that distorts them or completely overshadows them. The text presents the methods for extracting the desired signals from the noise. Each new development includes examples and exercises that use MATLAB to provide the answer in graphic forms for the reader's comprehension and understanding.